Compliance with medical regimen among hematological cancer patients and its association with symptoms of posttraumatic stress disorder and adjustment disorder - Springer, Franziska; Esser, Peter; Friedrich, Michael; Ernst, Jochen; Platzbecker, Uwe; Vucinic, Vladan; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2023)
Background Hematological cancer patients must comply with extensive medical instructions to prevent cancer progression or relapse. Psychological comorbidities and patient characteristics have been shown to affect compliance. However, the impact of posttraumatic stress disorder (PTSD) and adjustment disorder (AjD) on compliance in cancer patients remains unclear. This study aims to evaluate compliance in hematological cancer patients more comprehensively and to investigate its association with PTSD and AjD symptomatology as well as sociodemographic and medical factors. Methods Hematological cancer patients were cross-sectionally assessed via validated questionnaires for PTSD (PCL-5) and AjD (ADMN-20), and three internally developed items on compliance with medical regimen, with two referring to compliance behavior and one item assessing perceived difficulties with complying. Each compliance item was analyzed descriptively. Multiple linear regression models tested the association between compliance and PTSD and AjD symptomatology, sociodemographic and medical factors. Results In total, 291 patients were included (response rate 58%). Nine out of ten patients reported to either never (67%) or rarely (25%) change their medical regimen. However, 8% reported to change it once in a while or often. Compliance behavior was mostly rated as very easy (36%) or easy (45%) to implement. Nevertheless, 19% perceived it to be partly difficult or difficult to follow medical regimen. Symptoms of AjD (β = 0.31, p < 0.001) were associated with more difficulties to comply. Higher compliance behavior in turn was associated with stem cell transplantation (SCT) treatment (β = −0.21, p < 0.001) and lower education (β = −0.19, p = 0.002). Conclusion Although most patients indicated that they comply with medical regimen, a considerable subgroup of patients indicated subjectively perceived difficulties and thus seem to require additional support in implementing medical instructions possibly through improved medical communication and patient health literacy or shared decision-making.